Optical fiber flowmeter based on a single mode-multimode-single mode structure - Olivero, Massimo; Bellone, Aurora; Bano, Andon; Vallan, Alberto; Perrone, Guido (Frontiers in Sensors, 2022)
Single mode-Multimode-Single mode (SMS) sensors have been attracted a relevant attention because of their simple manufacturing, their capability of sensing different quantities, and their enhanced sensitivity compared to the most common fiber optic sensor represented by Fiber Bragg Gratings (FBGs). Moreover, SMS sensors exhibit blue-shift sensitivity to strain, opposite to FBGs, making them suitable in applications where strain-temperature cross-sensitivity may be an issue. SMS sensors are made by splicing a short multimode, preferably a two mode or quasi two-mode, optical fiber jumper between single mode pigtails. The interference of the modes propagating at different phase velocities produces a spectral pattern that shifts with temperature, strain or any perturbation of the phase difference among the modes. In this paper we review the main features of SMSs as temperature sensors and we present a potential biomedical application in an all-fiber flowmeter based on the hot-wire principle: a fiber-coupled laser source at 980 nm is used as a controllable heating source of the SMS sensor that, when immersed in fluid flow, converts the temperature variation, caused by the heat removal, into a wavelength shift of the transmitted spectrum. Thermal characterization and proof-of-concept experiments show the feasibility and functionality of the sensor and provide an outlook on possible developments and potential applications.